Pengembangan Pembelajaran Model Holistik Berbasis Karakter - Andi Sukmawati Atjo; Rismawati MS (TA'DIBAN, 2026)
Strengthening character education is one of the main focuses of basic education in Indonesia, including at the Madrasah Ibtidaiyah (MI) level. However, the implementation of character education in learning still faces various obstacles, such as the dominance of cognitive-oriented learning, the lack of integration of character values in the learning process, and the lack of a learning model that is able to develop the intellectual, social, emotional, spiritual, and moral aspects of students in an integrated manner. This research aims to develop a character-based holistic learning model that is valid, practical, and effective to be applied to Madrasah Ibtidaiyah students. The research uses the Research and Development (R&D) method with the ADDIE model which includes the Analysis, Design, Development, Implementation, and Evaluation stages. Data was collected through observation, interviews, documentation, questionnaires, and expert validation. Data analysis was carried out descriptively, quantitatively, and qualitatively by measuring the level of validity, practicality, and effectiveness of the model. The results of the study show that the character-based holistic learning model developed obtained a very valid category based on expert assessment, very practical based on the implementation of learning and teacher responses, and effective in improving the character of students. The developed model integrates religious values, responsibility, discipline, cooperation, social care, and independence through meaningful learning experiences. The novelty of this research lies in the development of a learning model that integrates a holistic approach, character education, madasah culture, and family involvement in one structured learning system. The research findings contribute to the development of innovative learning models that support the implementation of the Pancasila Student Profile and the Rahmatan lil Alamin Student Profile at the Madrasah Ibtidaiyah level.